Pengaruh Reputasi Auditor dan Rasio Dana Pemerintah terhadap Audit Delay dengan Ukuran Perguruan Tinggi Sebagai Variabel Moderasi - Dyah Novia Nugraheni; Anggie Kencana Putri (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2020)
This study aims to determine the effect of the auditor's reputation and the ratio of government funds to audit delay in the Legal Entity State University (PTNBH) with the size of universities as moderating. The population of this research is all PTNBH for the period of 2016-2018. The type of research is field research using quantitative methods. The population in this study was PTN within the Ministry of Education and Culture, namely 122 PT with the sample of this research was 11 PTNBH. The data used is secondary data obtained from the official website of PTNBH for an independent Public Accountant report. Methods of data analysis and hypothesis testing were performed using the SPSS 25 program, all hypotheses were tested using Moderated Regression Analysis (MRA) moderated regression analysis. The results showed that the Auditor's Reputation had a positive effect on Audit Delay, as did the Government Fund Ratio positively affecting Audit Delay. The moderating variable shows that the size of the college is not able to moderate the effect of the auditor's reputation on audit delay. However, the size of the college is able to moderate (strengthen) the effect of government funds on audit delay.